Cognitive Reserve Capacity: Exploring and Validating a Theoretical Model in Healthy Ageing. (7th May 2019) - McGarrigle, Lisa; Irving, Kate; van Boxtel, Martin P.J.; Boran, Lorraine
Abstract: Objective: Cognitive reserve (CR) capacity can be viewed as the maximum processing potential of neural systems that support adaptive cognitive performance in age-related cognitive decline. CR is a complex construct that can only be measured indirectly. Proxy measures (e.g., psychosocial/lifestyle variables) are traditionally used to reflect CR. However, strong relationships have been observed between these measures and cognitive functions (e.g., executive function [EF], processing resources [PR], fluid/crystallized abilities); therefore, the organizational structure of indicators implicated in CR remains unclear. The objective of this study was to test a hypothetical, theoretical model of CR capacity that includes both traditional CR proxy indicators and measures of cognitive function [Satz et al. (2011). Journal of Clinical and Experimental Neuropsychology, 33 (1), 121–130], which remain, as yet, untested.Method: Construct validity of the model was investigated in healthy older adults through exploratory and confirmatory factor analysis (EFA and CFA) using data from the Maastricht Ageing Study (MAAS). A secondary CFA was conducted to validate the model using data from the Irish Longitudinal Study on Ageing (TILDA).Results: EFA and CFA in MAAS established a two-factor model comprising EF/PR and cumulative cognitive enrichment (CCE), which was further validated in a secondary analysis in TILDA. Convergent and discriminant validity was supported in MAAS (range of R 2 = .228–.635; factor correlation confidence interval (CI) = .622, .740) and TILDA (range of R 2 = .172–.899; factor correlation CI = .559, .624).Conclusions: A dual model of CR elucidated the relationships between hypothesized indicators of CR capacity and revealed a two-factor structure suggesting that both control (EF/PR) and representational processes (CCE) are involved in CR capacity.